Education and Eminence in British Medicine. Issue 5780 (16th October 1971) - Hudson, L.; Jacot, B.
Abstract : The educational background of eminent members of the British medical profession was examined by recourse to Who's Who . Substantial differences in background were found among the various medical specialties. Members of specialties enjoying high prestige within the profession—physicians, surgeons—were more likely than other members of the sample to have been to an English school as opposed to one in Scotland, Wales, or Northern Ireland, and to a headmasters' conference school as opposed to a grammar school. Educational background was also found to relate to the aspect of the patient's body on which specialists normally worked. Specialists coming from English headmasters' conference schools were more likely than others to work on living bodies rather than dead bodies or parts of bodies, on the head rather than on the lower trunk, on male bodies rather than female bodies, and on the body's surface rather than its inside.